2008
DOI: 10.1038/ajh.2007.65
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure Response to Transcendental Meditation: A Meta-analysis

Abstract: The regular practice of Transcendental Meditation may have the potential to reduce systolic and diastolic blood pressure by approximately 4.7 and 3.2 mm Hg, respectively. These are clinically meaningful changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
113
6
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(130 citation statements)
references
References 29 publications
4
113
6
7
Order By: Relevance
“…On the other hand, an obvious example where control is minimal is the phenomenon of nighttime dreaming, likely in part to be the result of short bursts of activity in subgroups of name networks that are excited by weak and momentary stimuli from other connected name and sensory pathways. Finally, it could also be speculated that the name pathway model may adequately explain some elements of additional phenomena such as, to provide just one example, psychosomatic control ascribed to meditative thought (Anderson et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, an obvious example where control is minimal is the phenomenon of nighttime dreaming, likely in part to be the result of short bursts of activity in subgroups of name networks that are excited by weak and momentary stimuli from other connected name and sensory pathways. Finally, it could also be speculated that the name pathway model may adequately explain some elements of additional phenomena such as, to provide just one example, psychosomatic control ascribed to meditative thought (Anderson et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Categories were not at all, moderately and extremely *Response=moderately or extremely Participants were asked to "tell the behavior or behaviors that describe how you deal with racism?" Categories were never, rarely, sometimes fairly often, and very often ǂResponse=sometimes, fairly often, or very often transcendental meditation can be implemented through community health clinics is needed [36].…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis on blood pressure response to TM, researchers found that the use of TM compared to a control was associated with a systolic blood pressure reduction of -4.7mm Hg and diastolic blood pressure of -3.2 mm Hg at the 95% CI [21]. Transcendental meditation uses a repeated word or sound (mantra) to improve focus and achieve calmness when done twice a day for 20 min [22].…”
mentioning
confidence: 99%
“…Buoyed by the Maharishi's rise to Western fame in the late 1960's, the transcendental meditation (TM) movement predates the mindfulness movement by several decades, and appears to promote a range of health benefits ranging from lowering blood pressure to improving cognitive flexibility [16]. TM is perhaps best known in the research literature for its ability to promote relaxation and reverse physiological markers of chronic stress [17], outperforming related practices in promoting relaxation [18]. MSMT differs from TM by de-emphasizing relaxed, focus attention as a proximal goal, emphasizing instead the cultivation of awareness leading to insight into the nature of reality and one's conditioning within it [19].…”
Section: The Salutary Claimmentioning
confidence: 99%